Temperament and character in patients with borderline personality disorder taking gender and comorbidity into account - Barnow, Sven; Herpertz, Sabine; Spitzer, Carsten; Stopsack, Malte; Preuss, Ulrich W.; Grabe, Hans Jörgen; Kessler, Christoph; Freyberger, Harald J. (Psychopathology, 2007)
Borderline. Temperament and character. Psychobiological mode